2020
DOI: 10.21037/apm-20-1054
|View full text |Cite
|
Sign up to set email alerts
|

Variations in vital signs at the end of life in non-cancer patients: a retrospective study

Abstract: Background: The prediction of impending death is important for providing appropriate end-of-life care; however, limited information is currently available on the signs of impending death in non-cancer patients.Furthermore, although vital signs are routinely measured in clinical practice, changes in vital signs in the dying phase in non-cancer patients have not yet been elucidated in detail. Methods:We herein conducted a retrospective study to clarify changes in vital signs before death in noncancer patients. N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, no study has investigated the prognosis prediction accuracy by focusing on continuous measurement of respiratory and heart rates using a nonwearable monitor in dying cancer patients during the last days of life, excepting two studies for non-cancer patients. 12,13 In recent years, reviews that examine the association between changes in vital signs and patient outcomes by utilizing technology have been published. These include palliative cancer patients to monitor early changes in their conditions, 14 cancer survivors to summarize the effectiveness of behavioral trials, 15 and non-cancer patients to detect early deteriorations.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no study has investigated the prognosis prediction accuracy by focusing on continuous measurement of respiratory and heart rates using a nonwearable monitor in dying cancer patients during the last days of life, excepting two studies for non-cancer patients. 12,13 In recent years, reviews that examine the association between changes in vital signs and patient outcomes by utilizing technology have been published. These include palliative cancer patients to monitor early changes in their conditions, 14 cancer survivors to summarize the effectiveness of behavioral trials, 15 and non-cancer patients to detect early deteriorations.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent findings on terminal noncancer patients revealed that vital signs exhibited similar changes in the last seven days of life in cancer and noncancer patients. 20 Noncancer patients may have a similar clinical course, including physical signs, as terminal cancer patients in the last days of life. Therefore, the SID in terminal cancer patients may be applied to end-of-life prognostication in noncancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, no study has investigated the prognosis prediction accuracy by focusing on continuous measurement of respiratory and heart rates using a non-wearable monitor in dying cancer patients during the last days of life, excepting two studies for non-cancer patients. 12,13 In recent years, reviews that examine the association between changes in vital signs and patient outcomes by utilizing technology have been published. These include palliative cancer patients to monitor early changes in their conditions, 14 cancer survivors to summarize the effectiveness of behavioral trials, 15 and non-cancer patients to detect early deteriorations.…”
Section: Introductionmentioning
confidence: 99%